Aquatecture : architecture and water - Wylson, Anthony (Architectural Press, 1986)
Aquatecture: Architecture and Water examines the concept of aquatecture from both historical and contemporary viewpoints. The book is comprised of six chapters that discuss topics concerning architecture in aquatic environment. Chapter 1 reviews cultural and historical context that shaped the understanding of the water element. Chapters 2 and 3 discuss the urban waterfront, the interface between urban life and coast or river. The book also tackles water environment where water is used for visual effect and amenity value. Water techniques and water space for effects and design are then dealt wi.